2019
DOI: 10.1002/bem.22194
|View full text |Cite
|
Sign up to set email alerts
|

Effects of RF‐EMF on the Human Resting‐State EEG—the Inconsistencies in the Consistency. Part 1: Non‐Exposure‐Related Limitations of Comparability Between Studies

Abstract: The results of studies on possible effects of radiofrequency electromagnetic fields (RF‐EMFs) on human waking electroencephalography (EEG) have been quite heterogeneous. In the majority of studies, changes in the alpha‐frequency range in subjects who were exposed to different signals of mobile phone‐related EMF sources were observed, whereas other studies did not report any effects. In this review, possible reasons for these inconsistencies are presented and recommendations for future waking EEG studies are ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 111 publications
1
24
0
Order By: Relevance
“…These results indicate that the scattering of microwave in the brain functional sites leads to the polarization and depolarization of the brain tissue cell fluid, resulting in the change in dielectric constant and conductivity, which in turn changes the characteristics of microwave scattering to achieve the purpose of imaging [ 19 ]. Some recent reports have addressed the fact that microwave scattering has a significant effect on resting state EEG, particularly on the fact that the power of the EEG increases in the alpha band [ 24 , 25 ]. Exposure to electromagnetic fields can cause changes in the sleep EEG power [ 26 ], thereby suggesting that electromagnetic waves may affect brain function and the recovery process involved in sleep.…”
Section: Introductionmentioning
confidence: 99%
“…These results indicate that the scattering of microwave in the brain functional sites leads to the polarization and depolarization of the brain tissue cell fluid, resulting in the change in dielectric constant and conductivity, which in turn changes the characteristics of microwave scattering to achieve the purpose of imaging [ 19 ]. Some recent reports have addressed the fact that microwave scattering has a significant effect on resting state EEG, particularly on the fact that the power of the EEG increases in the alpha band [ 24 , 25 ]. Exposure to electromagnetic fields can cause changes in the sleep EEG power [ 26 ], thereby suggesting that electromagnetic waves may affect brain function and the recovery process involved in sleep.…”
Section: Introductionmentioning
confidence: 99%
“…Biological effects are occasionally observed at relatively high exposure levels close to, or above, the ICNIRP guidelines in experimental studies suggesting that RF-EMF may modify-at least temporary-oxidative stress responses or membrane potentials (Barnes & Greenebaum, 2020). However, this has not been found to translate inevitably to health damage, and reviews reporting such sporadic effects could not identify consistency in terms of exposure time and intensity or other testing conditions, for instance for cognitive behavior in laboratory animals (Sienkiewicz & van Rongen, 2019) or for electrophysiological effects in humans (Danker-Hopfe et al, 2019;Wallace & Selmaoui, 2019). Various reviews concluded that the excellence of conceptional and experimental execution inversely correlates with the likelihood to report an effect; the more the quality criteria requirements were satisfied in a study, the smaller was the number of detected response in cells or animals (Elwood & Wood, 2019;Simko et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…If RF-EMF below regulatory limits would cause symptoms, other mechanisms would need to be involved. Physiological effects such as oxidative stress, radical pair mechanisms, or alterations of the human electroencephalogram have been described to occur below regulatory limits but a link to symptoms is not established ( Barnes and Greenebaum, 2020 , Danker‐Hopfe et al, 2019 , Dasdag and Akdag, 2016 , Wallace and Selmaoui, 2019 ).…”
Section: Introductionmentioning
confidence: 99%